Business online community credibility model of an online consumption community using linear programming for effective customer relationship management. (1st January 2014) - Alavi, Shirin
In the present era there has been significant technological advancements which led to the move towards mobile and multiple screens, the era of online paradigm and the trend of the cloud whereby everybody expects access to data anytime, anywhere enabled via the cloud, this has changed the way business is done today. Organisations are waking up to the need of extending business processes beyond corporate firewalls which implies inclusion of people outside the company as readily as they do people inside the firm thus giving rise to the formation of various online consumption communities. In this research paper, a business online community credibility (BOCC) model was developed by incorporating the perspective of the community manager to measure the credibility of an online consumption community by incorporating the concepts of community dynamics, co-creation, collaboration enabler, CRM goals, return on investment and customer life time value.